Her hidden children: the rise of Wicca and paganism in America - Clifton, Chas S. (The Pagan studies series, 2006)
How the ravens came to the lake: Wicca's birth and Atlantic passage -- Calling it "nature religion" -- The rhetoric of Wicca -- The playboy and the witch: Wicca and popular culture -- West Coast Wicca, self-invention, and the "Gardnerian magnet" -- A search for paradise: other new pagan religions -- Final thoughts